2018
DOI: 10.1016/j.avsg.2017.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vascular Calcifications on Long Femoropopliteal Stenting Outcomes

Abstract: The study showed that VC quantification with CT imaging is feasible and useful for comparing outcomes following PAD endovascular revascularization. Below a certain threshold, the presence of VC might be necessary for plaque stability and may protect against in-stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…), which is commonly used for endovascular treatment of lower limb PAD, as it may hinder the delivery/transfer of the anti-proliferative agent to the arterial wall. 25,56,57 Therefore, as arterial vessel calcification constitutes an independent predictor of EVT failure, 55,58 additional therapeutic modalities have been introduced to optimize EVT results, including but not limited to specialty balloons, and IVL. 24,[59][60][61][62] These devices offer debulking and/or modification of the atherosclerotic plaque facilitating as such balloon angioplasty and/or stent expansion, while also improving the arterial wall penetration of anti-proliferative agents (eg, paclitaxel) when drug-eluting devices are utilized [eg, drug coated balloons (DCB), drug-eluting stents (DES)].…”
Section: The Burden Of Calcified Target Lesionsmentioning
confidence: 99%
“…), which is commonly used for endovascular treatment of lower limb PAD, as it may hinder the delivery/transfer of the anti-proliferative agent to the arterial wall. 25,56,57 Therefore, as arterial vessel calcification constitutes an independent predictor of EVT failure, 55,58 additional therapeutic modalities have been introduced to optimize EVT results, including but not limited to specialty balloons, and IVL. 24,[59][60][61][62] These devices offer debulking and/or modification of the atherosclerotic plaque facilitating as such balloon angioplasty and/or stent expansion, while also improving the arterial wall penetration of anti-proliferative agents (eg, paclitaxel) when drug-eluting devices are utilized [eg, drug coated balloons (DCB), drug-eluting stents (DES)].…”
Section: The Burden Of Calcified Target Lesionsmentioning
confidence: 99%
“…Patel et al, 2015, found that the burden of calcified plaque, but not soft or fibrocalcific plaque, was related to restenosis, reintervention, and amputation-free survival of PAD patients, highlighting the importance of CT plaque analysis in risk stratification for patients undergoing femoropopliteal endovascular procedures [29]. Kaladji et al, 2018, using patients from the STELLA and STELLA PTX registries, discovered that patients with severe vascular calcification (vascular calcification rate > 20%) were associated with early in-stent thrombosis (<1 month), while patients with no vascular calcification (vascular calcification rate < 1%) were associated with late stent thrombosis (6-24 months) [30]. He et al, 2019, found that among patients who received pre-operative CTA, those with a high calcified plaque burden had a higher risk for unfavorable outcomes, including in-stent restenosis, amputation, and mortality [31].…”
Section: Ct For Plaque Calcification Assessmentmentioning
confidence: 99%
“…• Maximal iliac angulation: measured using a 3D reconstruction • Percentage of iliac calcification: determined using a specific measuring tool based on grayscale values of the Hounsfield scale (5) A severity grade of 0 to 3 was assigned to each calculated value, as per Chaikof's standards.…”
Section: Measurements Used To Categorize Patientsmentioning
confidence: 99%